Fresh water snail of Pachychilidae Troschel, 1857 (Gastropoda-Prosobranchia-Cerithioidea) in Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2014)
Based on analysing snail samples of Pachychilidae recently collected from many locatlities of Vietnam, at the same time with revision on taxonomy of this family, research results show that Pachychilidae has 15 species belong to 6 gennera in Vietnam: Adamietta delavayana (Heude, 1888); Adamietta housei (Lea, 1856); Adamietta reevei (Brot, 1874); Adamietta swinhoei (Adams, 1870); Brotia costula (Rafinesque, 1833); Brotia hamonvillei (Brot, 1887); Brotia jullieni (Deshayes, 1874); Brotia siamensis (Brot, 1886); Paracrostoma solemiana (Brandt, 1968); Paracrostoma pseudosulcospira (Brandt, 1968); Semisulcospira aubryana (Heude, 1888); Sulcospira hainanensis (Brot, 1872); Sulcospira proteus (Bavey et Dautzenberg, 1910); Sulcospira touranensis (Souleyet, 1852); and Stenomelania dautzenbergiana (Morlet, 1884). The key of identifation for fresh water snails of Pachychilidae in Vietnam and some remarks on taxonomic status of these species as well as genera: Adamietta, Brotia, Paracrostoma, Semisulcospira, Stenomelania and Sulcospira are given also in this paper.